Adsorption of epoxiconazole and tebuconazole in twenty different agricultural soils in relation to their properties - Bošković, Nikola; Brandstätter-Scherr, Kerstin; Sedláček, Petr; Bílková, Zuzana; Bielská, Lucie; Hofman, Jakub (Chemosphere, 2020)
Conazole fungicides are currently used pesticides with considerable chronic toxicity and ecotoxicity that are also on EU list for substitution. They enter the soil forming short- or long-term residues. In this study two of their representatives, epoxiconazole (EPC) and tebuconazole (TBC), have been tested with 20 soils from the Czech Republic for their adsorption. Adsorption, by means of Kd coefficients, was compared to "basic" (TOC, pH, clay …) and "advanced" (surface area, minerals ..) soil properties. After doing multivariate analysis of the variables it was apparent that adsorption of both pesticides was highly associated with pH (negatively correlated), and less associated with soil organo-mineral complex (TOC, clay and surface area) and C and N in soil organic matter (OM). Particle sizes or cation exchange capacity (CEC) did not show correlation with adsorption, but showed an association in multidimensional space in factor analysis (FA). Some correlations were revealed between EPC adsorption and soil organic matter parameters. Recalculating Kd to Koc and to Gibb's free energy (ΔG) and its values indicated that the adsorption of EPC and TBC is mainly weak physical adsorption - partitioning. Also, ΔG values gave better correlation with pH(H2O) than Kd. Surface area impacted EPC adsorption. From the several soil minerals, kaolinite showed EPC and TBC adsorption. EPC adsorption was not highly influenced with pH changes compared to TBC. The number and types of H-bonds with molecular geometry govern the sorption, which might crucially affect leachibility in soil, and this may indicate that TBC is more leachable than EPC for the same soil.
Keywords: jíl; velikost částic; kationty; Soil Pollutants; zemědělství; Particle Size; Adsorption; Cations; triazoly; látky znečišťující půdu; epoxidové sloučeniny; Minerals; Triazoles; Czech Republic; Pesticides; minerály; Česká republika; Epoxy Compounds; Clay; Soil; půda; pesticidy; adsorpce; Agriculture